City of the queen : a novel of colonial Hong Kong - Shi, Shuqing, 1945- (Modern Chinese literature from Taiwan., 2005)
After being kidnapped from her home in rural China, Huang is taken to Hong Kong and sold into prostitution. Yet thanks to her shrewd, sometimes devious business dealings and several twists of fate, she overcomes these cruel beginnings and finds success as a wealthy landowner. What follows is the epic story of Huang's family, lived under the shadow of colonialism. Adam Smith, a British officer, struggles with the competing seductions of Huang's beauty and British respectability; Qu Yabing, Smith's servant, despises anything Chinese, yet becomes Huang's lover; Huang's devoutly Christian daughter-in-law tries to redeem the sins she believes Huang has committed; and her great-granddaughter, a quintessential Hong Kong youth, turns her back on tradition to revel in the pleasures of the metropolis. In this unconventional and compelling tale, acclaimed Taiwanese writer Shih Shu-ching captures the rich detail and unique tensions of a vividly evolving Hong Kong.